Macroalgal microbiomes unveil a valuable genetic resource for halogen metabolism - Anna Lavecchia; Bruno Fosso; Aschwin H. Engelen; Sara Borin; Caterina Manzari; Ernesto Picardi; Graziano Pesole; Antonio Placido (Microbiome, 2024)
Abstract Background Macroalgae, especially reds (Rhodophyta Division) and browns (Phaeophyta Division), are known for producing various halogenated compounds. Yet, the reasons underlying their production and the fate of these metabolites remain largely unknown. Some theories suggest their potential antimicrobial activity and involvement in interactions between macroalgae and prokaryotes. However, detailed investigations are currently missing on how the genetic information of prokaryotic communities associated with macroalgae may influence the fate of organohalogenated molecules. Results To address this challenge, we created a specialized dataset containing 161 enzymes, each with a complete enzyme commission number, known to be involved in halogen metabolism. This dataset served as a reference to annotate the corresponding genes encoded in both the metagenomic contigs and 98 metagenome-assembled genomes (MAGs) obtained from the microbiome of 2 red (Sphaerococcus coronopifolius and Asparagopsis taxiformis) and 1 brown (Halopteris scoparia) macroalgae. We detected many dehalogenation-related genes, particularly those with hydrolytic functions, suggesting their potential involvement in the degradation of a wide spectrum of halocarbons and haloaromatic molecules, including anthropogenic compounds. We uncovered an array of degradative gene functions within MAGs, spanning various bacterial orders such as Rhodobacterales, Rhizobiales, Caulobacterales, Geminicoccales, Sphingomonadales, Granulosicoccales, Microtrichales, and Pseudomonadales. Less abundant than degradative functions, we also uncovered genes associated with the biosynthesis of halogenated antimicrobial compounds and metabolites. Conclusion The functional data provided here contribute to understanding the still largely unexplored role of unknown prokaryotes. These findings support the hypothesis that macroalgae function as holobionts, where the metabolism of halogenated compounds might play a role in symbiogenesis and act as a possible defense mechanism against environmental chemical stressors. Furthermore, bacterial groups, previously never connected with organohalogen metabolism, e.g., Caulobacterales, Geminicoccales, Granulosicoccales, and Microtrichales, functionally characterized through MAGs reconstruction, revealed a biotechnologically relevant gene content, useful in synthetic biology, and bioprospecting applications. Video Abstract